Negotiating grey spaces: A southernised relational analysis of customary land-use regulation mechanisms in peri-urban Informal mixed-use developments - A case study of the Helderberg District in Cape Town - Geyer, H. S. (Stellenbosch : Stellenbosch University, 2021)
Thesis (PhD)--Stellenbosch University, 2021.